2015
DOI: 10.1002/jms.3640
|View full text |Cite
|
Sign up to set email alerts
|

Rapid structural characterization of in vivo and in vitro metabolites of tinoridine using UHPLC–QTOF–MS/MS and in silico toxicological screening of its metabolites

Abstract: Tinoridine is a nonsteroidal anti-inflammatory drug and also has potent radical scavenger and antiperoxidative activity. However, metabolism of tinoridine has not been thoroughly investigated. To identify in vivo metabolites, the drug was administered to Sprague-Dawley rats (n = 5) at a dose of 20 mg kg(-1), and blood, urine and feces were collected at different time points up to 24 h. In vitro metabolism was delved by incubating the drug with rat liver microsomes and human liver microsomes. The metabolites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The in vitro metabolite generation studies were performed according to reported methodology . To conduct the in vitro metabolism study, 25 μL of HLM and RLM suspensions (20 mg mL −1 ) were added to two different Eppendorf tubes containing 420 μL of 100 mM phosphate buffer (pH 7.4), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro metabolite generation studies were performed according to reported methodology . To conduct the in vitro metabolism study, 25 μL of HLM and RLM suspensions (20 mg mL −1 ) were added to two different Eppendorf tubes containing 420 μL of 100 mM phosphate buffer (pH 7.4), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are no reports on the detailed identification and characterization of in vitro and in vivo metabolites. This has prompted us to undertake comprehensive metabolite profiling of VLZ using ultrahigh‐performance liquid chromatography (UHPLC)/quadrupole time‐of‐flight (QTOF) tandem mass spectrometry (MS/MS) . The toxicity of each metabolite was predicted by an in silico tool so as to ascertain their toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The first three are NSAIDs used in the treatment of pain and inflammation. Tinoridine and Tiaprofenic acid act by inhibiting COX enzymes [ 26 , 30 ], and Tinoridine presents potent antiperoxidative and radical scavenger activity [ 30 ], while Zileuton is a LOX inhibitor [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro metabolite studies were performed according to reported methodology in HLM and RLM . To conduct this study, 25 μl of HLM, RLM suspension (20 mg ml −1 ) was added to two different Eppendorf tubes containing 420 μl of 100 mM phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%